Phytochemical screening of alkaloid compounds on microencapsulation of Moringa oleifera leaf extract - Halim, Rita; Suzan, Raihanah; Hanina; Dewi, Hasna; Ekawaty, Fadliyana; Hafizah; Hardiningsih, Denok Tri (Proceedings Academic Universitas Jambi, 2025)
Background: Moringa oleifera leaves are rich in bioactive compounds, including alkaloids. Alkaloid compounds are crucial for their pharmacological potential and role as natural antioxidants in improving food quality and stability. Objective: This study aimed to examine the presence of alkaloid compounds in the microencapsulation of Moringa oleifera leaf extract as a strategy to protect active compounds from degradation and retain their nutritional benefits. Methods: The Moringa oleifera leaf extract was formulated into microencapsulation using the freeze-drying method. Phytochemical screening for alkaloid compounds was performed using the Dragendorff, Bouchardat, and Wagner tests. Results: The phytochemical screening results confirmed the presence (positive) of alkaloid compounds in the microcapsule preparation. This positive result was characterized by the formation of an intense orange-red precipitate (Dragendorff), a reddish-brown precipitate (Bouchardat), and a brown precipitate (Wagner). Conclusion: The microencapsulation of Moringa oleifera leaf extract successfully presented positively detected alkaloid compounds. The retention of alkaloids as antioxidants in these microcapsules provides a strong foundation for their development as supplements or fortification ingredients in food products to enhance nutritional value.